2017
DOI: 10.1089/hum.2016.139
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Oxidants Distinguishes Susceptibility of Prostate Carcinoma Cell Lines to p53 Gene Transfer Mediated by an Improved Adenoviral Vector

Abstract: Previously, the authors developed an adenoviral vector, Ad-PG, where transgene expression is regulated by a p53-responsive promoter. When used to transfer the p53 cDNA, a positive feedback mechanism is established. In the present study, a critical comparison is performed between Ad-PGp53 and AdRGD-PGp53, where the RGD motif was incorporated in the adenoviral fiber protein. AdRGD-PGp53 provided superior transgene expression levels and resulted in the killing of prostate carcinoma cell lines DU145 and PC3. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Silencing of PIG3 increased expression of PTEN and reduced PI3K and phosphorylated AKT, it was suggested that PIG3 induces ROS at intermediate levels, which induces phosphorylation of AKT and activation of mTOR [ 93 ]. We have observed that PIG3 is induced by p53 in prostate cancer, but its expression is not a key factor for induction of apoptosis [ 94 ].…”
Section: Regulation Of Metabolism By P53mentioning
confidence: 99%
See 2 more Smart Citations
“…Silencing of PIG3 increased expression of PTEN and reduced PI3K and phosphorylated AKT, it was suggested that PIG3 induces ROS at intermediate levels, which induces phosphorylation of AKT and activation of mTOR [ 93 ]. We have observed that PIG3 is induced by p53 in prostate cancer, but its expression is not a key factor for induction of apoptosis [ 94 ].…”
Section: Regulation Of Metabolism By P53mentioning
confidence: 99%
“…PIG3 and PIG6 are downstream targets of p53 that induce oxidants production; however, others and we have observed that expression of these genes is not essential to induction of apoptosis. We have observed that NADPH oxidase, especially NOX1, is induced by p53 and can induce apoptosis of prostate cancer cell lines [ 94 ]. Figure 3 shows how in normal conditions p53 activates genes involved in ROS detoxification and under stress p53 induces genes that increase ROS to toxic levels that induce cell death.…”
Section: Regulation Of Metabolism By P53mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, animal experiments have shown that NOX1 is positively associated with tumorigenesis and malignant behavior in prostate cancer. Furthermore, in recent years, in vitro models using adenovirus vectors have shown that NOX1 plays a role in the cell death of prostate cancer cells [ 83 ], and NOX1 has been associated with metastatic potential in a series of cell lines developed from LNCaP [ 81 ].…”
Section: Pathological Significance Of the Nox Family In Urologicalmentioning
confidence: 99%
“…Moreover, placing the p53 cDNA under the control of the p53-responsive promoter (PGTxβ, or simply PG) establishes an autoregulatory, positive feedback mechanism that was shown to outperform vectors employing a constitutive promoter to express p53. That is, gene expression and cell killing in vitro and in vivo were superior when using our modified vectors to express p53 [104][105][106]. We have also looked to p19ARF (alternate reading frame, p19ARF in mice and p14ARF in humans), a functional partner of p53, to serve as the death-promoting factor in our approach and have observed that it is effectively expressed from our p53-responsive vectors in tumor cells that harbor wild type p53, resulting in activation of p53-mediated cell killing in vitro and in vivo [107].…”
Section: Turning Gene Therapy Into Immunotherapy: Adenovirus-carryingmentioning
confidence: 98%